New furocarbazole alkaloids from Lonicera quinquelocularis - Khan, Dilfaraz; Khan, Shafiullah; Badshah, Syed; Ullah, Hazrat; Ullah, Hamid; Muhammad, Zia; Woodward, Simon (Taylor & Francis, 2016)
Two new furocarbazole alkaloids, 3-formyl-6,7-dimethoxy-furo[1,2]carbazole (1) and methyl-6,7-dimethoxy-furo[1,2]carbazole-3-carboxylate (2), along with two known carbazole alkaloids, 3-formyl-2-hydroxy-7-methoxycarbazole (3) and methyl 2,7-dimethoxycarbazole-3-carboxylate (4) were isolated from the ethyl acetate soluble fraction of Lonicera quinquelocularis. Their structures were established on the basis of spectroscopic analysis.